Antibody-Conjugated Nanoparticles for Therapeutic Applications - Cardoso, Maria Margarida Canas Mendes de Almeida (2017)
Ines Peca is grateful for financial support from Fundacao para a Ciencia e a Tecnologia through contract SFRH/BD/48773/2008. This work has been supported by Fundacao para a Ciencia e a Tecnologia through grant no. PEst-C/EQB/LA0006/2011.